Color analysis in creations fashion audiovisuals from artistic expression (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2023)
This text was written in the context of a research project on the audiovisual creation known as fashion film. The main objective is to highlight the use of technologies for the creation of static and moving images as a vehicle for artistic expression by artists who create audiovisual pieces related to fashion and, specifically, to the fashion film. In order to achieve the proposed objective, an analysis of the audiovisual creations L'Elélégance (sic) by Sonia Delaunay (1925) and Esencia de una seducción by Eugenio Recuenco (2008) is proposed from the perspective of the audiovisual media as a way of artistic expression. The main results of the analysis suggest that colour is an essential element in the creation of the tale and expression for the artist, elevating it to the same level of prominence as the characters themselves. Furthermore, it is noticed that the technology and the resources available to the artists are involved in and form part of the final artwork.
Keywords: Fashion film; Sonia Delaunay; Eugenio Recuenco; artistic expression; matte painting; Keller-Dorian